Microsoft Office Excel 2003 - Coulthard, Glen J. (McGraw-Hill Technology Education, 2004)
The Advantage Series presents the Feature-Method-Practice approach to computer software applications to today's technology and business students. This series implements an efficient and effective learning model, which enhances critical thinking skills and provides students and faculty with complete application coverage.